A banner flap with adjacent rotation flap for closure of circular skin defects: a schematic comparison with conventional rotation flap technique. Issue 5 (1st October 2021) - Aizawa, Tetsushi; Hirayama, Takahiro; Tojo, Shota; Kiyosawa, Tomoharu
Abstract: The local flap method is a minimally invasive, quick, and common technique of closing skin defects. Several methods using multiple local flaps are employed for the purpose of closing relatively large defects, and minimizing the resultant scar and deformity. We present a combined local flap method using a banner flap with an adjacent rotation flap (B-R flap) with the potential for closing circular defects. A retrospective analysis was performed in 15 patients treated with the B-R flap for circular skin defects over a 2-year period. The sizes of the flap and the healthy skin excision area were evaluated using image analysis software, and were compared to a model of a conventional rotation flap that would be necessary to close the same defect. All flaps were successfully engrafted. The B-R flap required a 39.1% smaller rotation flap and an 85.9% smaller area of healthy skin compared to the conventional rotation flap technique. There was one adverse event, partial epidermal necrosis that was conservatively treated and healed. The B-R flap is comparatively less invasive; it allows a smaller area of healthy skin to be excised. It can be a useful option for closing a circular defect.